Analisis Pola Penjualan Barang Teknologi Informasi (TI) Menggunakan Algoritma FP-Growth - Rizky Wandri; Anggi Hanafiah (IT Journal Research and Development, 2022)
Determination of sales patterns is very important in marketing. Sales pattern serves to conduct an effective analysis in improving marketing. Sales analysis aims to explore new knowledge that can help design effective strategies by utilizing sales transaction data. This study processes sales data for 12 transaction days containing 47 items using the Fp-Growth algorithm. The results of this study are items with a minimum value of support > 0.10 and confidence 0.60 and will be compared with testing data using RapidMiner to test whether the results are valid so that the test results can help in designing sales strategies.